Invasive Molar Pregnancy in a Woman Aged 55 Years: A Case Report - Hristova, M.; Bozhilov, S.; Hristov, N.; Tancheva, Y.; Ivanova, N.; Penkova-Radicheva, Mariana (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Gestational trophoblastic diseases (GTDs) are a group of rare human tumors by abnormal trophoblastic proliferation. GTD is neoplasia that develops from the trophoblastic element of blastocyst. In this case, some specific features of the trophoblast are retained, while the hCG (Human Chorionic Gonadotropin) synthesis and invasion potential of the underlying tissues are preserved. CASE REPORT: We reported a 55-year-old patient with invasive (destructive) mole hydatidiform “FIGO I” with invasion in myometrium wall. This diagnostic was suggested by abnormal (dysfunctional) vaginal bleeding, amenorrhea period, and low abdominal pain. Our paraclinical investigation was physical examination, transabdominal, and transvaginal ultrasound and complete blood count. Transabdominal and transvaginal ultrasound reveal enlarged uterus volume, with dimensions 18/12/5 cm and with Doppler rich blood supply through myometrium and endometrium. Therapeutic method applied was abdominal hysterectomy and bilateral salpingo-oophorectomy. Anatomopathological report revealed a complete invasive mole. After the surgical intervention, the patient was no treated with methotrexate as prophylactic chemotherapy (recommended by oncologists) because the level of β-hCG was very low. CONCLUSION: Examining the tissue after a miscarriage in women at extreme ages should raise a suspicion of mole. Molar pregnancy should be excluded in these cases.